Clicking on Heaven's Door: The Effect of Immigrant Legalization on Crime - Paolo Pinotti (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
We estimate the effect of immigrant legalization on the crime rate of immigrants in Italy by exploiting an ideal regression discontinuity design: fixed quotas of residence permits are available each year, applications must be submitted electronically on specific 'Click Days', and are processed on a first-come, first-served basis until the available quotas are exhausted. Matching data on applications with individual- level criminal records, we show that legalization reduces the crime rate of legalized immigrants by 0.6 percentage points on average, on a baseline crime rate of 1.1 percent.
Keywords: J61; K37; K42; 330; legal status; crime; regression discontinuity design